Editorial: Women in Business in India AABFJ Volume 13, Issue 2, 2019 - Gurinder Singh; Bhawna Kumar; Hima Bindu Kota (Australasian Accounting, Business and Finance Journal, 2019)
Volume 13, Issue 2, Special Issue, Women in Business in India.
Keywords: Editorial; Volume 13; Issue 2; Special Issue; Women in Business in India.